(untitled) (The Conference Hub, 2026)
This in the article commerce banks information in systems use management and restriction processes modern at risk-based approaches through improvement issues illuminated. Research within information in systems use management risk model in the process based on organization done protection mechanism exemplary structure shaped and in practice wide being used there is models disadvantages analysis Commercial banks information to systems typical real time in mode performance , high transaction density and information to safety to be placed strict requirements in consideration taken , risks to time dependency and variability into account recipient improved risk model offer Also , based on semantic mapping information only to format to bring directed and via API use restriction in the process information integration SMART-Q algorithm providing working issued . Proposal done approach commerce banks information in systems risks more precisely evaluation , errors fast identification , integration processes simplification and use restriction efficiency increase opportunity gives .